The Effect of Work Stress and Work Motivation on the Employees Work Productivity - M. Hafidz; Mokhamad Arwani (Faculty of Economics and Business, Universitas Wahid Hasyim, 2025)
The objective of this study is to ascertain the impact of work stress and motivation on the productivity of employees at PT Jinlin Luggage Indonesia. Work productivity is a critical metric for evaluating employee performance, as it directly influences the realization of organizational objectives. It is widely accepted that elevated levels of work stress, coupled with diminished levels of job motivation, have the potential to diminish employee productivity. The present study employs a quantitative approach, using a survey method. The sampling technique employed is a census, where in the entire population of the Quality Control department, consisting of 45 employees, serves as the sample. The research instrument employed was a questionnaire that utilized a Likert scale. The data analysis technique employed is multiple linear regressions, with the assistance of SPSS software. The findings suggest that work-related stress exerts a substantial negative influence on work productivity, concurrently; work motivation exerts a substantial positive influence on work productivity in PT Jinlin Luggage Indonesia. These results underscore the pivotal role of company management in fostering stress resilience and enhancing work motivation, thereby maximizing employee productivity.